Building anti-stunting youth awareness - Puji Ati, Endang; S Tagoli, Mutia; Tonote, Musdalifa; Sofyan, Sulis; Tahir, Yunisa; Yusnita Batjo, Farahdila; Rindi Sahea, Hana; Evjulin Samadi, Gracia (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
Background: Stunting is a state of malnutrition related to inadequate nutrients in the past, so it is classified as a chronic nutritional problem. Efforts to reduce the risk of stunting include increasing the adequacy of nutritional needs of infants, toddlers and adolescents in the womb. Objective: The purpose of implementing this program is to improve the health of adolescents and reduce the risk of nutritional deficiencies and stunting. Method: The method used during the implementation of this community service program is the lecture and discussion method with various stages. Results: The implementation of the Brazilian spinach empowerment program is a program that attracts the attention and interest of the community due to the relatively short cultivation method with a choice of processing with or without cooking first. Conclusion: The management of Brazilian spinach or amaranthus sp., which is carried out in a more varied way, will increase adolescents' interest in consuming vegetables. This will also reduce the risk of haemoglobin deficiency and stunting in the future due to inadequate nutrition.